Study on the effect of additives on the properties of mortar used in 3D printing technology with a small-diameter nozzle - Nguyen Duc Tuan; Huynh Phuong Nam; Nguyen Thanh Binh; Nguyen Minh Hai (Tạp chí Khoa học và Công nghệ)
3D printing in construction simplifies processes by removing formwork, enabling precise automation, and supporting complex structural designs. This study evaluates the effect of admixtures on the properties of mortar used in 3D printing with a nozzle diameter of 5mm. The plasticizing additive Sika Plastiment 96 and the shrinkage-reducing admixture Sika Intraplast Z-HV, at varying dosages, were employed to design 20 mortar mix trials. A series of experiments were conducted to assess the flowability, retention of flowability, load-bearing capacity of printed layers, and mechanical strength of the mortar. The results indicate that the dosage of admixtures significantly affects the printability and compressive-flexural strength of the hardened mortar. The optimal admixture ratio of Intraplast Z-HV and Plastiment-96 was determined to be 0.6:0.45%, the designed mortar mix retained printability for up to 40 minutes with a 5mm nozzle, and the maximum number of layers printable in one session was 20.